The durability properties of oil palm shell lightweight aggregate concrete containing coal bottom ASH - Nurul Atikah Shafika, Jamil (2019)
Oil palm shell (OPS) and coal bottom ash (CBA) is an industrial waste product. This waste material generated electricity from the burning of this waste for the purpose of their mill. The usage of CBA as partial sand replacement in the mixture of concrete can helped to reduce pollution to the environment. This research was to investigate the effect of usage CBA as partial sand replacement on durability properties of the OPS concrete. There were two types of the concrete mixture used which is OPS concrete with 100% river sand and OPS concrete containing CBA as partial sand replacement. Percentages of CBA as partial sand replacement for sand were 0%, 10%, 20%, and 30%. All the specimens undergo curing which was air curing until the time for testing. All specimens were being tested in terms of water absorption, porosity and acid resistance. OPS concrete with 10% of CBA as partial sand replacement had a lowest percentage of water absorption which is 1.305%. For porosity, OPS concrete with 10% of CBA as partial sand replacement had a lowest percentage which is 5.88%. And for acid resistance, OPS concrete with 10% of CBA as partial sand replacement had a lowest percentage which is 3.376%. Conclusion, the usage of suitable amount of CBA as partial sand replacement increase the durability of OPS concrete in terms of water absorption, porosity and acid resistance.